Factors affecting credit card usage: a case study at Jusco Seremban 2 / Puteri Nur Azatul Ashikin Mansor Ahmad - Mansor Ahmad, Puteri Nur Azatul Ashikin (Faculty of Business and Management, 2018)
Credit cards have become a necessity to the public and the number of credit cards approved has increased recently. Some people claims that by having a numbers of credit cards, it will reflect someone socio economy status. Due to that factor, it had led to the increment of credit card debts. Therefore, it is time to look into this matter. This study attempt to find factors of credit card usage which is lifestyle, easy access, knowledge, reward that influence the consumer at Jusco Seremban 2. Data for the study were collected through self-administered survey and online survey using Google docs. SPSS Statistics 20 are used to analyse the data. This study finds that lifestyle, easy access and reward have a relationship with credit card usage. However, knowledge does not have a association with credit card usage. In conclusion, Malaysian government should tighten the guideline of approving credit card by a commercial bank. The continuous education on the impact of credit card debt to Malaysian should be done regularly. Commercial banks must play their role in advising the credit card holders on the advantages and the disadvantages of using the credit cards.